Ascertainment of Appropriate GRC Structure for Two Area Thermal System under Seagull Optimization based 2DOF-PID Controller - Kalyan, Ch.Naga Sai; Syed, Khamruddin; Goud, B. Srikanth; Reddy, Ch. Rami; Shahinzadeh, Hossein; Gharehpetian, Gevork B. (2021 7th International Conference on Signal Processing and Intelligent Systems (ICSPIS), 2021)
This paper attempted to assess the performances of two simulation models of generation rate constraint (GRC) for two area thermal systems to achieve optimal load frequency control (LFC). The dynamical models of GRC investigated in this work are coined as open loop and closed loop GRC which are extensively utilized by the researchers without providing specific analysis for their selection and suitability. This paper facilitates the selection of appropriate and most effective GRC structures based on dynamical analysis about the thermal system to obtain LFC optimally. Two area thermal system has been examined with different GRC models in the platform of MATLAB/SIMULINK under supervision of two degrees of freedom (DOF)-PID (2DOF-PID) controller optimized with seagull optimization algorithm (SOA). Simulation results demonstrate the most suitable GRC model for the thermal system to obtain optimal LFC.